1987
DOI: 10.1177/002580248702700403
|View full text |Cite
|
Sign up to set email alerts
|

Victims of Violence: A Demographic and Clinical Study

Abstract: This study is an attempt to evaluate the psychiatric sequelae in victims of violence in Northern Ireland between 1979 and 1984. Seven hundred and nineteen consecutive referrals for medico-legal reports were investigated using detailed analysis of case records. These clients were all seeking compensation for psychological injury allegedly sustained following a violent incident. Details of demographic data, diagnosis and utilization of treatment services were recorded. Clients showed a high rate of anxiety and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…• • exacerbation of personality traits (Kee et al, 1987), a proportion in keeping with the 20-30% quoted in a recent paper by Adshead (2000).…”
Section: Depressive Statesupporting
confidence: 81%
See 2 more Smart Citations
“…• • exacerbation of personality traits (Kee et al, 1987), a proportion in keeping with the 20-30% quoted in a recent paper by Adshead (2000).…”
Section: Depressive Statesupporting
confidence: 81%
“…Sims, in a smaller study of victims of the Birmingham bomb, found that 5% required psychiatric help (see Curran, 1988). In a large survey of 499 criminal injury litigants who had each been victim of a variety of acts of terrorist and criminal violence, we found that 4.5% required psychiatric in-patient admission, while 11% graduated to NHS out-patient services (Kee et al, 1987). In our most recent survey of 2191 victims, 2% were admitted and 13% referred to either psychiatric out-patients, community psychiatric nurses or counselling services (further details available from the author upon request).…”
Section: Impact On Servicesmentioning
confidence: 83%
See 1 more Smart Citation